Green Porous Composite for Combining Ion Exchange-Adsorptive Removal of Zinc Ions from Aqueous Solutions - Ibrahim, Nargis H.; Al-Jubouri, Sama M. (Iraqi Journal of Science, 2024)
A low-cost, effective green porous composite was prepared and used for the sorption of Zn+2 ions from aqueous solutions. The effect of contact time, sorbent dosage, initial ion concentration, solution pH, and temperature on the sorption of Zn+2 ions was investigated. The results showed higher removal efficiency of Zn+2 ions (83%), which was achieved at a contact time of 120 minutes, a normal pH of 6.4, and a temperature of 313 K. The Langmuir isotherm model successfully described the experimental results of the sorption process with a theoretical maximum sorption capacity of 4.819 mg/g. The kinetics of sorption showed that the pseudo-second-order model fitted the experimental results better than the pseudo-first-order model. The intra-particle diffusion kinetics indicated that the boundary film was the rate-determining step of the sorption process. The thermodynamic parameters showed that the sorption of Zn+2 ions was spontaneous and endothermic under the studied conditions. The solidification of spent composite by kaolin was able to keep the leachate cations at an acceptable level in the solution after 12 weeks of exposure to a salty medium.